Midnight over Sanctaphrax / 3. - Stewart, Paul, 1955- (Stewart, Paul, 1955- Edge chronicles, 2004)
Twig, a young sky pirate captain, is the only one who can save the floating city of Sanctaphrax from the Mother Storm.